Adaptability of root morphology and growth of two forage grass species in response to salt stress - Zhang, Yang; Zhang, Yanfang; Zhang, Rui; Song, Yingying; Li, Gang; Song, Yayun; Ma, Guochen; Guo, Huizhen (Frontiers in Environmental Science, 2024)
The cultivated Echinochloa frumentacea (Roxb.) Link and Echinochloa crusgalli (L.) Beauv. var. mitis (Pursh) Peter are two valuable grass species that are widely used in improving saline-alkali soil. Here we conducted a pot experiment combined with roots morphological analysis to investigate the adaptability of grass roots to saline stress environments, with cultivated E. frumentacea and E. crusgalli being subjected to salt treatments of 0 (CK), 100, 220, and 340 mmoL• L -1 . Results indicated that E. frumentacea had longer primary roots with fewer root hairs and lower local branching density than E. crusgalli, with the root volume of E. frumentacea being 1.43 times greater than that of E. crusgalli. The aboveground biomass of both grasses decreased significantly (p < 0.05) with increasing salt concentrations, whereas the root-to-shoot ratio exhibited the opposite trend, suggesting the preferential allocation of photosynthetic products to the roots under salt stress. The total length, surface area, and tip number of fine roots and the growth of coarse roots (d >2.00 mm) showed significant differences (p < 0.05) between the two grass species. Different concentrations of salt stress had inconsistent effects on the biomass and radial growth of roots for grasses. The cultivated E. frumentacea seems to adopt an adapt strategy of gradually increasing its root thickness, root hairs, and root density under increasing salt stress. E. crusgalli, on the other hand, employed a strategy of increasing root length, maintaining uniform thickness, and developing root hairs.